Intergenerational social mobility and body mass index trajectories - A follow-up study from Finland - J. Salmela; T. Lallukka; N. Kanerva; O. Pietiläinen; O. Rahkonen; E. Mauramo (Elsevier, 2021)
Evidence remains unclear on how intergenerational social mobility is associated with body mass index (BMI) and its long-term changes. Our study identified BMI trajectories from middle to older age by intergenerational social mobility groups and stratified the analyses by gender and two birth cohorts (birth years 1940‒1947 and 1950-1962). We used questionnaire-based cohort data that consists of four survey phases: 2000-2002, 2007, 2012, and 2017. In Phase 1, participants were 40-60-year-old employees of the City of Helsinki, Finland. Our analytical sample consisted of 6,971 women and 1,752 men. Intergenerational social mobility was constructed based on self-reported parental and own education-both divided into high and low-yielding four groups: stable high socioeconomic position (SEP) (high-high), upward social mobility (low-high), downward social mobility (high-low), and stable low SEP (low-low). BMI was calculated from self-reported height and weight from all four phases. Using mixed-effects linear regression, we found increasing BMI trajectories in all four social mobility groups until the age of 65. Women and men with stable high SEP had lower BMI trajectories compared to those with stable low SEP. In the younger birth cohort, women with upward social mobility had a lower BMI trajectory than women with stable low SEP. Additionally, women and men with downward social mobility had higher BMI trajectories than those with stable high SEP. In the older birth cohort, however, the BMI trajectories of upward and downward social mobility groups were somewhat similar and settled between the BMI trajectories of stable high and stable low SEP groups. Our results indicate that the associations between intergenerational social mobility and BMI may depend on gender and birth cohort. Nevertheless, to reduce socioeconomic inequalities in unhealthy weight gain, obesity prevention actions that focus on people who are likely to remain in low SEP might be worthwhile.